Trimalchio's feast and other mini-mysteries - Lawrence, Caroline (London : Orion Children's Books, 2007)
A collection of short mysteries that follow the adventures of Flavia and her friends in Rome during the reign of Emperor Titus.
The case of the missing coin -- Trimalchio's feast -- Jonathan vs. Ira -- The case of the citrus-wood table -- The case of the talking statue -- Death by Vespasian.
5.6
5-8
Keywords: Historical fiction; Mystery and detective stories; Historical fiction; Mystery fiction; Rome -- History -- Empire, 30 B.C.-476 A.D. -- Juvenile fiction; Rome -- History -- Empire, 30 B.C.-476 A.D. -- Fiction; Rome -- History -- Fiction; Historical fiction; Mystery fiction